STUDY OF PRE-STACK DEPTH MIGRATION IN THE COMPLEX STRUCTURE - KOMANG ANDIKA ARIS PERMANA (NIM 12403021), I
Migration is one of many methods in seismic processing for subsurface imaging. Initial seismic processing using data in time domain, in the fact geology structure is in depth domain. Processing data in depth domain important to reposition truth reflector in subsurface, and in some case geology image structure in depth domain used to occur volume of reservoir. Determine precise imaging of geology subsurface, will be difficult if the structure is complex with high lateral velocity variation. This problem will be influence in migration phase, especially in Pre Stack Depth Migration. Purpose of this paper is doing analysis in migration, especially in Pre Stack Depth Migration phase. The analysis of migration used synthetic and real data with complex structure and significant lateral velocity variation. Velocity model building, using HVA (Horizon Velocity Analysis) method and Time-Depth curve from well data. The precise of reflector reposition are depending by velocity quality. Reposition reflectors to the truth position using Pre Stack Depth Migration method, better than Post Migration or Pre Stack Time Migration.